Essai sur la définition d’un statut juridique de la procédure de dédouanement des envois postaux - Bedet, Florian (Université Paris-Saclay, 2016)
La thèse entreprise a pour objectif d’essayer de définir un statut juridique de la procédure de dédouanement des envois postaux. La nature juridique des envois postaux justifie un traitement douanier autonome et distinct des formalités douanières applicables aux marchandises des échanges commerciaux internationaux. Les travaux réalisés devraient tout d’abord aider à répondre aux problématiques liées aux difficultés juridiques de la définition de cette procédure de dédouanement spécifique et leurs conséquences. L’étude portera particulièrement sur le règlement des différends entre les autorités douanières et les importateurs ou exportateurs d’envois postaux internationaux en cas de litige lié au dédouanement. Au préalable, il faut donc relever et clarifier les règles juridiques qui sont déjà applicables au dédouanement des envois postaux, tant au niveau national et européen, qu'au niveau international en ce domaine. Cependant, cela se révèle difficile, et il faut rester opiniâtre devant l'extrême diversité des sources et des textes, parsemés dans de nombreuses branches du droit. Il faut ensuite nécessairement tenter de redéfinir, clairement et simplement, la notion d’envoi postal et la notion de service postal universel justifiant l'application d'une procédure spécifique de dédouanement des envois postaux. La notion de service postal universel implique un dédouanement rapide des envois postaux. Les administrations douanières ont, elles, l’obligation d’assurer le contrôle de toutes les marchandises importées ou exportées de leurs territoires nationales. La mission principale des autorités douanières est de protéger l’attractivité économique des Etats. Les agents douaniers doivent, d’une part, prélever les droits de douane et taxes à l’importation, d’autre part, lutter contre les trafics illicites de marchandises prohibées ou soumises à restriction. La délicate combinaison de l’universalisme du service postal et des obligations douanières doit permettre la reconnaissance et l’établissement d’une procédure de dédouanement spécifique aux envois postaux impliquant une nouvelle détermination des envois relevant du service postal universel et la mise en place de règles de dédouanement obligatoires et communes à l’ensemble des services postaux internationaux. La mise en œuvre d’une coopération internationale renforcée entre les services postaux et les autorités douanières est, en ce sens, préalablement indispensable. L’étude doit permettre de rendre compréhensible, pour les entreprises et les particuliers nationaux et européens, le droit positif douanier applicable au dédouanement postal. On analysera notamment les infractions et les règles douanières sanctionnant les diverses fraudes que l’on retrouve le plus fréquemment en pratique. L’essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux démontrera qu’il est impératif de renforcer les pouvoirs et les moyens de contrôle et de sanctions des autorités douanières pour ce type singulier de dédouanement. Les voies de recours non-contentieuses et contentieuses qui sont ouvertes aux redevables et requérants feront également l’objet d’un traitement particulier. Les droits des redevables ou requérants sont notamment garantis par le principe de contrôle de la légalité des décisions de l’Administration des douanes et de ses agents par le juge judiciaire. Le juge judiciaire et le droit européen limitent et encadrent les pouvoirs exorbitants des autorités douanières.
Keywords: Commerce international; Contentieux douanier; Coopération; Coopération internationale; Droits de douane; Fraud; Fret; Litigation; Mailings; Postal customs clearance; Postes; Service postal universel; Taxes and customs duties; Taxes et droits de douane à l'importation; Universal postal service; Échanges commerciaux internationaux

Essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux - Bedet, Florian (Université Paris-Saclay, 2016)
La thèse entreprise a pour objectif d’essayer de définir un statut juridique de la procédure de dédouanement des envois postaux. La nature juridique des envois postaux justifie un traitement douanier autonome et distinct des formalités douanières applicables aux marchandises des échanges commerciaux internationaux. Les travaux réalisés devraient tout d’abord aider à répondre aux problématiques liées aux difficultés juridiques de la définition de cette procédure de dédouanement spécifique et leurs conséquences. L’étude portera particulièrement sur le règlement des différends entre les autorités douanières et les importateurs ou exportateurs d’envois postaux internationaux en cas de litige lié au dédouanement. Au préalable, il faut donc relever et clarifier les règles juridiques qui sont déjà applicables au dédouanement des envois postaux, tant au niveau national et européen, qu'au niveau international en ce domaine. Cependant, cela se révèle difficile, et il faut rester opiniâtre devant l'extrême diversité des sources et des textes, parsemés dans de nombreuses branches du droit. Il faut ensuite nécessairement tenter de redéfinir, clairement et simplement, la notion d’envoi postal et la notion de service postal universel justifiant l'application d'une procédure spécifique de dédouanement des envois postaux. La notion de service postal universel implique un dédouanement rapide des envois postaux. Les administrations douanières ont, elles, l’obligation d’assurer le contrôle de toutes les marchandises importées ou exportées de leurs territoires nationales. La mission principale des autorités douanières est de protéger l’attractivité économique des Etats. Les agents douaniers doivent, d’une part, prélever les droits de douane et taxes à l’importation, d’autre part, lutter contre les trafics illicites de marchandises prohibées ou soumises à restriction. La délicate combinaison de l’universalisme du service postal et des obligations douanières doit permettre la reconnaissance et l’établissement d’une procédure de dédouanement spécifique aux envois postaux impliquant une nouvelle détermination des envois relevant du service postal universel et la mise en place de règles de dédouanement obligatoires et communes à l’ensemble des services postaux internationaux. La mise en œuvre d’une coopération internationale renforcée entre les services postaux et les autorités douanières est, en ce sens, préalablement indispensable. L’étude doit permettre de rendre compréhensible, pour les entreprises et les particuliers nationaux et européens, le droit positif douanier applicable au dédouanement postal. On analysera notamment les infractions et les règles douanières sanctionnant les diverses fraudes que l’on retrouve le plus fréquemment en pratique. L’essai sur la définition d'un statut juridique de la procédure de dédouanement des envois postaux démontrera qu’il est impératif de renforcer les pouvoirs et les moyens de contrôle et de sanctions des autorités douanières pour ce type singulier de dédouanement. Les voies de recours non-contentieuses et contentieuses qui sont ouvertes aux redevables et requérants feront également l’objet d’un traitement particulier. Les droits des redevables ou requérants sont notamment garantis par le principe de contrôle de la légalité des décisions de l’Administration des douanes et de ses agents par le juge judiciaire. Le juge judiciaire et le droit européen limitent et encadrent les pouvoirs exorbitants des autorités douanières.
Keywords: Commerce international; Contentieux douanier; Coopération; Coopération internationale; Droits de douane; Fraud; Fret; Litigation; Mailings; Postal customs clearance; Postes; Service postal universel; Taxes and customs duties; Taxes et droits de douane à l'importation; Universal postal service; Échanges commerciaux internationaux

The liability of trade unions for conduct of their members during industrial action - Mlungisi, Ernest Tenza (University of South Africa, 2016)
South Africa has been experiencing a number of violent strikes by trade unions in recent times. The issue is not only to hold unions liable for damage caused during strikes, but also to reduce the number of violent strikes. This study investigates if victims of such violence can hold trade unions liable for the violent acts committed by their members during industrial action. The Labour Relations Act, 66 of 1995 (LRA) makes provision for the dismissal of employees who commit misconduct during an unprotected strike. It also provides the remedy of an interdict and a claim for just and equitable compensation which can be made against the union, during an unprotected strike. It is further possible to hold the union together with its members liable for damages in terms of the Regulation of Gatherings Act, 205 of 1993 (RGA). The study argues that a strike or conduct in furtherance of a strike that becomes violent could lose protection and the trade union should consequently be held liable, in terms of the LRA and/ or the RGA, for damages caused by its members. This study investigates the position in Canada, Botswana and Australia to determine if there could be any other basis upon which to hold trade union liable for the conduct of its members. The study recommends that the common law doctrine of vicarious liability should be developed by the courts to allow trade unions to be held liable for damages caused by members during violent industrial action. Policy considerations and changing economic conditions and the nature of strikes in the Republic favours the expansion of the doctrine of vicarious liability to trade union member relationship.
Keywords: Common law; Industrial relations; Interest arbitration; Labor unions; Liability (Law); Secret ballot requirement; South Africa; Strikes and lockouts; Tort liability of labor unions; Trade union denial; Trade union liability

The United Nations Convention on the Use of Electronic Communications in International Contracts at Ten: Practical Relevance and Lessons Learned - Castellani, Luca G. (Journal of Law, Society and Development, 2016)
The United Nations Commission on International Trade Law prepared the first global treaty specifically devoted to electronic commerce law, the United Nations Convention on the Use of Electronic Communications in International Contracts. That treaty builds on the highly successful UNCITRAL Model Law on Electronic Commerce and the UNCITRAL Model Law on Electronic Signatures. This article describes the main goals of the Electronic Communications Convention and its scope of application. In particular, it illustrates how that Convention may fully enable the use of electronic means under other widely adopted treaties such as the Convention on the Recognition and Enforcement of Foreign Arbitral Awards and the United Nations Convention on Contracts for the International Sale of Goods. The article also describes the main substantive provisions of the Electronic Communications Convention, in particular clarifying how that Convention updates and completes the provisions of the UNCITRAL Model Law on Electronic Commerce. This Model Law is the backbone of electronic commerce law in numerous countries and a de facto legislative standard insouthern Africa. Finally, the article describes the manner (or patterns) in which the adoption of the Electronic Communications Convention takes place. It stresses that, while the Convention is often used as a source of inspiration for domestic law reform, in order for it to achieve all its intended goals, its formal adoption as a treaty is necessary. The final message is therefore a call upon all states to consider the adoption of that Convention in order to support the broader use of electronic means, especially in the light of the implications for economic development and the promotion of paperless trade.
Keywords: Convention adoption patterns; Digital signatures; Electronic communications; Electronic contracting; Legal harmonisation

The Attitude of OHADA Law Countries Towards the CISG - Kahindo, Nguru Aristide (Journal of Law, Society and Development, 2016)
Disparities in national laws are likely to result in uncertainty which, in turn, creates obstacles to international commerce. It is acknowledged that strong investment flows cannot be achieved without a secure legal and commercial environment. Mindful of such a need, states decided to harmonise sales law internationally. To this end, in 1980 they adopted the United Nations Convention on Contracts for the International Sale of Goods known as the Vienna Sales Convention or the CISG. The CISG has led a number of countries, including the Organisation for the Harmonisation of Business Law in Africa (OHADA) law states, to modernise their local sales law. However, only three of 17 countries that constitute the OHADA community have ratified the CISG. OHADA law countries give the impression of favouring a more regional approach to the unification of sales law rather than the CISG™s global approach by implementing a local Commercial Uniform Act. Their indifference towards the CISG is not without consequences for commerce in the OHADA region. This article seeks to demonstrate that the lack of ratification of a universal convention, as for example the CISG, poses a danger to commercial dealings. It also intends to show that the CISG is not hostile to regional uniform sales laws of the OHADA Commercial Uniform Act type. It concludes that OHADA countries do not need to be afraid of their acceptance of the CISG and recommends that it be ratified.
Keywords: Business law; CISG; Commercial Uniform Act; Harmonisation; OHADA law; Uniform sales law

The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.

Connectivité et accès au marché international : cas des pays de la Communauté économique monétaire de l'Afrique centrale (CEMAC) - Djam’Angai, Ludé (Université Cheikh Anta Diop, 2016)
Cette thèse a pour objectif général d 'analyser les effets de la connectivité sur l'accès au marché international des pays de la CEMAC. D'une part, elle expose les effets de la connectivité physique sur les échanges et, d'autre part, elle présente le rôle joué par les institutions dans la connectivité et la facilitation des échanges. En utilisant le modèle de gravité augmenté sur la période de 2006-2013 à partir de la méthode de Pseudo Maximum de Vraisemblance de la Loi de Poisson (PPML), les résultats d 'estimations économétriques ont pu montrer que la CEMAC reste un espace peu connecté et cette faible connectivité constitue un obstacle à ses échanges. De plus, afin de mener à bien notre régression, l'analyse en composante principale (ACP) a été utilisée pour calculer un indice de connectivité physique de transport, de démontrer l'hétérogénéité infrastructurelle et spatiale de la CEMAC, et de classer les pays les plus connectés de la zone.
Keywords: ACP; CEMAC; Connectivité; Marché international; Modèle de gravité

Commerce international et investissements directs étrangers : complémentarité ou substituabilité ? - Tayara, Saeed (Université de Poitiers, 2016)
Ce travail étudie, théoriquement et empiriquement, l'interaction entre le commerce international et l'investissement direct étranger (IDE), interaction qui a été un des principaux canaux de la mondialisation économique et de l'essor des chaînes de valeur mondiales dans la segmentation des activités de production. Les modèles théoriques montrent que le commerce international et les IDE peuvent se développer dans une relation de substituabilité ou de complémentarité. La nature de cette relation peut être la conséquence de facteurs exogènes, déterminants de la spécialisation des pays, ou le résultat de la stratégie endogène des firmes dans l'organisation de leurs activités à l'international. La validation empirique s'appuie sur une adaptation du modèle de gravité, en appliquant les techniques économétrique sur données de panel sur des données bilatérales pour la France au cours de la période de 1993 à 2012. Les estimations mettent en évidence une relation de complémentarité entre le commerce et l'IDE au niveau le plus agrégé. Cependant, une analyse comparative à un niveau plus désagrégé permet de trouver des indices de substituabilité et de complémentarité selon les groupes de pays partenaires.
Keywords: Commerce extérieur; Commerce international; Complementarity; Complémentarité; Données de panel; Entreprise multinationale; Entreprises multinationales; Foreign direct investment; Gravity model.; International Trade; Investissement étranger direct; Investissements étrangers; Modèle de gravité; Modèles économétriques; Multinational firm; Panel data; Substituabilité; Substitutability

A Convenção de Viena sobre contratos de compra e venda internacional de mercadorias e o papel do Estado no projeto de uniformização do Direito Privado Internacional - Bertotti, Daniela (Pontifícia Universidade Católica de São Paulo, 2016)
The present study aims at analyzing the United Nations Convention on Contracts for the International Sale of Goods (CISG) by examining most thoroughly the different interpretations of its text on the light of several western legal traditions. This analysis of the implications of such different interpretations will give rise to a discussion on the level of interpenetration among different legal systems. This, in turn, leads to an analysis of the impact of the conditions imposed by the Convention on its interpretation, which is considered a selfcontained autonomous ruling within the text of the Convention. As can be seen from a historical overview of the matter, the pursuit of unified regulations governing the international purchase and sale of goods is precisely the result of trade practices and of the consolidation of customary laws and principles. This thesis is thus based on the dynamics of this unifying process. The analysis will focus on its innovative feature of a consonant interpretation; an important structural element which may determine the success or failure of the text of the Convention when observed in different legal environments. It will be taken into consideration the role of the relation between governments and their institutions established with International Organizations, as well as that of the need for predictability when signing international agreements. Therefore, elements such as sovereignty and globalization are essential for a proper understanding of the impacts of this Convention in international law, namely, international trade laws
Keywords: CISG; Contracts; Contrato Internacional de Compra e Venda; Direito internacional privado; International Sales of Goods; Interpretation; Interpretação; United Nations Convention on Contracts

The CISG as a Model Law: A Comparative Law Approach - Chianale, Angelo (Singapore Journal of Legal Studies, 2016)
In this article I adopt a comparative law approach to illustrate the coexistence of various models governing the sale of goods, and their classification on the basis of two main characteristics: the transfer of property and the opposition certainty/flexibility. I use this approach to analyse the United Nations Convention on Contracts for the International Sale of Goods. 1 Then I examine how theCISG influenced several national systems and can influence future attempts at regional harmonisation. I conclude with the reasons that in my opinion make the CISG a good model for the sale of goods (prestige, equilibrium and derogability), and with the desirable future developments.

Teaching Transnational Commercial Law in the African Context - Eiselen, Sieg (University of Western Australia Law Review, 2016)

The Admission and Enrolment of Foreign Legal Practitioners in South Africa under the Legal Practice Act: International Trade Law and Constitutional Perspectives - Hagenmeier, Cornelius; Shumba, Tapiwa; Mireku, Obeng (Potchefstroom Electronic Law Journal, 2016)
Globalisation requires ever closer co-operation between legal professionals hailing from different national jurisdictions. This interactive global environment has fostered growing international training and mobility among legal practitioners and the internationalisation of legal education. Increasing numbers of law students get trained in other countries as part of their undergraduate degrees or even come to foreign shores to obtain law degrees. Many students hailing from other African countries study towardsLLBdegrees at South African universities. Major commercial law firms ensure that they can offer in-house expertise on major foreign legal systems and co-operate with partner firms in other parts of the globe. The General Agreement on Trade in Services (GATS), to which South Africa is a party, is a multilateral agreement focusing on the liberalisation of trade in services amongst member countries. Services under the GATS system include legal services. The commitments made by South Africa under this agreement require that South Africa allows foreign legal practitioners to establish a commercial presence or be transferred to South Africa. The Bill of Rights entrenched in Chapter 2 of the South African Constitution guarantees fundamental rights including the right to equality and freedom of trade, occupation and profession. With the coming into force of the new Legal Practice Act 28 of 2014, which provides a legislative framework for regulating the affairs of legal practitioners, including their admission and enrolment, it is necessary to assess the extent to which the Act complies with the GATS rules and the South African Constitution. This paper examines the new Legal Practice Act 28 of 2014, and examines whether the Act addresses the conflicts that have always existed between the regulation of the legal profession and the admission of legal practitioners in South Africa with South Africa's commitments under the GATS system. Using the doctrinal legal method, it analyses and evaluates the rules governing the admission of foreign attorneys in South Africa from two perspectives. First, it considers them in the light of the international law obligations of the country and second it evaluates whether or not they comply with the South African Constitution, and more specifically with the Bill of Rights entrenched in the South African Constitution. While the new legislation may assist in ensuring the compliance of South Africa with the relevant GATS rules, it will depend on the regulations which still have to be promulgated to what extent the new legal framework will achieve the full compliance of South Africa with all relevant GATS rules. The paper concludes with recommendations for the reform of the Legal Practice Act. It argues that while the requirement to be a South African permanent resident in order to qualify for admission as an attorney may be justifiable in terms of GATS and in terms of South African constitutional law, it is not in South Africa's best interest to retain it. Consequently, the paper calls for the repeal of the permanent residence requirement for admission as an attorney in the county.
Keywords: Affirmative action; Designated groups; Employment equity; Equality; Minority group; Multi layered disadvantage; Situation sensitive

Transparency and dispute settlements : a study of the agreements on sanitary and phytosanitary measures and technical barriers to trade - Karttunen, Marianna (European University Institute, 2016)
Transparency of trade regulations by all WTO Members is essential for open, fair and predictable trade relations. Because of the negative integration process followed by the WTO Agreements, a myriad of different regulations apply in all WTO Members and have the potential of affecting international trade. With the progressive lowering of tariffs since 1947, these differing regulations remain the most significant barriers to trade, and the most difficult to reduce. The Agreements on Sanitary and Phytosanitary (SPS) measures and on Technical Barriers to Trade (TBT) provide the most comprehensive frameworks to address the costs arising from such regulatory diversity, through extensive obligations on regulatory transparency and cooperation and introducing elements of positive integration. Does transparency, within the SPS and TBT Agreements prevent disputes from rising, or ensure all Members access necessary information to raise more and better disputes? Through a presentation of the legal obligations and institutional framework of the two agreements (Part I), an in-depth analysis of the issues encountered by WTO Members in the implementation of the two Agreements and raised as trade concerns in the SPS and TBT Committees (Part II), and a study of the factors leading to disputes and transparency's role in addressing them (Part III), this thesis will demonstrate that transparency as it exists under the two agreements has the potential to both complement dispute settlement, by giving equal access to information for Members to raise disputes, and substitute dispute settlement, by fostering dialogue between Members before their frictions escalate to formal disputes. In this sense, the strength of the WTO legal and institutional system goes well beyond its dispute settlement system, with enforcement of WTO obligations fostered by better information sharing and dialogue among Members themselves, through non-judicial means.
Keywords: Food adulteration; Food inspection; Foreign trade regulation; Non-tariff trade barriers; Produce trade

Formation of Contract for the International Sales of Goods - Saleem, Saman Othman (Near East University, 2016)
The Convention for the International Sale of Goods called the Vienna Conference 1980 is an astute international statute that regulates the sale of goods globally. It has been ratified by about 83 countries of the world and countries that have not ratified it have at a point or the other made reference to it. Major economic players apart from England have ratified and have their courts pronounce on the CISG. The Convention provides for the well known elements of contract and also allows for the usage of standard user terms, for example, general terms known or related to certain goods. It is imperial to state that there are also certain regional statutes that are similar to the CISG although with varying differences. It is important to also mention that the CISG also has its lacunae and defects such as allowance for exemption, contents and so on. The CISG has been pronounced upon by courts across the world and has been seen to be highly justiciable.
Keywords: CISG; Convention; English Law; Iraq; United Nations

International Trade, WTO and Economic Development - Siddiqui, Kalim (World Review of Political Economy, 2016)
This article examines the existing literature on trade liberalisation and its effect on the economies of developing countries. It will also briefly examine the theory of comparative advantage which is seen as justification for global trade liberalisation under the auspices of the World Trade Organization. This process is also associated with greater openness, economic interdependence and deepening economic integration with the world economy. The study is important because once again the international institutions strongly advocate trade and financial liberalisation in developing countries. The proponents of trade liberalisation argue that multilateral trade negotiations would achieve these goals, and poor countries particularly would benefit from it. However, such policies may increase vulnerability and make developing countries further hostages of international finance capital. Adoption of open market policies in agriculture would also mean the abandoning of self-reliance and food sovereignty, which may have wider consequences in terms of food shortages, food prices and rural employment.